MOLECULAR DETECTION PROTOCOL OF SARS-COV-2 THROUGH SELF-COLLECTED SALIVA SPECIMENS VERSUS NASOPHARYNGEAL SWABS - GHIDOUCHE, Abderrezak; HALLOUCHE, Sarah; AIT-ALI, Djida; BOUDRAHEM-HANNOU, Lila; NOURI, Hamid; TLIBA, Souhil; BITAM, Idir; AMIROUCHE, Adel (African Journal of Infectious Diseases (AJID), 2024)
Background : Various detection methods, based on specific nucleotide sequences of SARS-CoV-2, were rapidly developed and used as emergency laboratory applications. The most common diagnostic method for detecting SARS-CoV-2 infection is real-time quantitative reverse transcriptase-polymerase chain reaction (RT-qPCR). Aims: Here, we carried out to assess the sensitivity and specificity of using saliva self-collected from adult and pediatric patients, as a biological sample for RT-PCR diagnosis. Methods: We compared the sensitivity and specificity of RT-qPCR from 85 samples of adult and pediatric patient, including nasopharyngeal swabs (NPS) and saliva. Results: Our RT-qPCR results provide that saliva samples showed the highest sensitivity followed by a nasopharyngeal swab for symptomatic as well as for asymptomatic adult patients. On the other hand, samples from symptomatic patients showed a higher sensitivity as compared to asymptomatic patients, while a cycle threshold (Ct) value exhibited a higher sensitivity as compared to higher Ct value. Together, including symptomatic and asymptomatic subjects, the overall agreement between the saliva sample and the nasopharyngeal is about 84%. Conclusion: The sensitivity of saliva samples remains acceptable; it may still be a viable option in locations where laboratory facilities are lacking for diagnostic purposes in the early phase of the disease.